2018
DOI: 10.1002/pmic.201800056
|View full text |Cite
|
Sign up to set email alerts
|

Time‐Resolved NMR Analysis of Proteolytic α‐Synuclein Processing in vitro and in cellulo

Abstract: Targeted proteolysis of the disordered Parkinson's disease protein alpha-synuclein (αSyn) constitutes an important event under physiological and pathological cell conditions. In this work, site-specific αSyn cleavage by different endopeptidases in vitro and by endogenous proteases in extracts of challenged and unchallenged cells was studied by time-resolved NMR spectroscopy. Specifically, proteolytic processing was monitored under neutral and low pH conditions and in response to Rotenone-induced oxidative stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…However, we did not observe the additional resonances for Tau40 in HEK-293T cells which was previously identified as a possible phosphorylation resonance of Tau40 modified in Xenopus laevis oocytes. A recent in-cell NMR study revealed that cell type specifically contributes to the biological and pathological behaviors of α-syn in different intracellular environments [6,50]. Therefore, different cell types may feature distinct intracellular environment as well as distinct post-translational modification systems.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not observe the additional resonances for Tau40 in HEK-293T cells which was previously identified as a possible phosphorylation resonance of Tau40 modified in Xenopus laevis oocytes. A recent in-cell NMR study revealed that cell type specifically contributes to the biological and pathological behaviors of α-syn in different intracellular environments [6,50]. Therefore, different cell types may feature distinct intracellular environment as well as distinct post-translational modification systems.…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of protein modification and in particular phosphorylation was put forward by Selenko in 2010 and has been used since then in a couple of applications (Kosten et al, 2014, p. 129;Landrieu et al, 2006;Liokatis et al, 2010;Mylona et al, 2016). Such studies are even possible in cellular environment by time-resolved in-cell NMR (Theillet et al, 2013).…”
Section: "Slow" Kineticsmentioning
confidence: 99%
“…Such studies are even possible in cellular environment by time-resolved in-cell NMR (Theillet et al, 2013). Other applications of time-resolved in-cell NMR are the proteolytic alpha-synuclein processing (Limatola et al, 2018), the methylation of lysines in cell, the investigation of ligand binding in cellular environment (Luchinat et al, 2020a(Luchinat et al, , 2020b) and the modulation of bound GTP levels of RAS (Zhao et al, 2020). Time-resolved NMR experiments are now also pursued to characterize metabolic flux in patient-derived primary cells (Alshamleh et al, 2020;Reed et al, 2019).…”
Section: "Slow" Kineticsmentioning
confidence: 99%